Rural Electrification Program in Indonesia: Comparing SEHEN and SHS Program - Maxensius Tri Sambodo (Institute for Economic and Social Research, 2015)
AbstractIn 2014, the Indonesian government has targets to obtain 80% of electrification ratio and 98.9% of rural electrification ratio. Extending the grid and off-grid connection has been done to obtain the targets. This paper aims to compare two main programs on rural electrification namely Super Extra Energy Saving (Super Ekstra Hemat Energi, SEHEN) that is belong to PLN (state owned company in electricity) and the Solar Home System (SHS) that is financed by the Ministry of Energy and Mineral Resources (MEMR). Indonesia has started the rural electrification program in the late 1950s, but how to provide electricity in a sustainable ways both organizationally and institutionally still become a big challenge. The experiences from East Nusa Tenggara provinces showed that both SEHEN and SHS can instantly improve electrification ratio, but government needs to synchronize the technical, administrative, and financial aspect from the two programs. Without any improvements in designing the program, we argue that the existing program is not sustainable.Keywords: Electrification Ratio; Rural Electrification; SustainabilityAbstrakTahun 2014, Pemerintah Indonesia menetapkan target pencapaian rasio elektrifikasi sebesar 80% dan rasio elektifikasi perdesaan sebesar 98.9%. Perpanjangan jaringan grid dan off-grid telah dilakukan sepagai upaya pencapaian target. Tulisan ini bertujuan membandingkan dua program elktifikasi perdesaan yang utama, yaitu Super Ekstra Hemat Energi (SEHEN) yang dimiliki PLN (Badan Usaha Milik Negara di bidang kelistrikan) dan Solar Home System (SHS) yang didanai Kementerian Energi dan Sumber Daya Mineral. Indonesia telah memulai program elektrifikasi perdesaan sejak akhir 1950an,namun masih menghadapi tantangan dalam menemukan cara elektrifikasi yang berkesinambungan secara organisasional maupun institusional. Pengalaman dari Provinsi Nusa Tenggara Timur menunjukkan bahwa SEHEN maupun SHS dapat meningkatkan rasio elektrifikasi secara signifikan, namun pemerintah masih harus menyelaraskan aspek teknis, administratif, dan keuangan dari kedua program. Tanpa pembenahan dari sisi rancangan, kami berpendapat bahwa program yang telah ada tidak ada bertahan.Kata kunci: Rasio Elektrifikasi; Listrik Perdesaan; KeberlanjutanJEL classifications: O10; Q40